A STUDY ON EFFECTS OF YOGA AND ACADEMIC ACHIEVEMENT OF HIGH SCHOOL STUDENTS - Jeba N, Christal (International Journal of Research -GRANTHAALAYAH, 2018)
The article focuses on assessing facts of a study on effects of yoga and academic achievement of high school students’. Transcendental meditation reduces stress and improves academic performance mentally causes increased alertness, and the practice of yoga brings improvement in competitive performance. It is inferred from the present investigation that all the high school students have average level of effect of yoga with respect to all the background variables under study. It was proved that students under consideration scored higher grades and had lower stress level as compared to the other students who do not practice yoga.